Beyond the Dogma of the Fixed Book Price Agreement - Frederick van der Ploeg (Center for Economic Studies and ifo Institute (CESifo), 2003)
After describing the essential features of the book market, a welfare analysis of the fixed book price agreement is given. Allowance is made for the opportunity cost of reading. Theoretically, the agreement pushes up book prices and depresses book sales. However, more titles will be published, particularly of books with low price elasticity and that take a long time to read. Potential advantages of better service, distribution and retail networks seem less relevant. The book market is one of imperfect competition, but even so the cross-subsidy argument is unlikely to be valid. A qualitative analysis of the Dutch situation is given. Tentative conclusions are that one should be more concerned about the number of well-stocked bookshops than the diversity of published titles and that debutantes do not face big barriers to entry. One should be even more concerned about the falling proportions of people reading books. Governments fail to set (quantitative) objectives for the fixed book price agreement, which makes it difficult to evaluate its success and contributes to it being treated as a dogma in the book world and the political arena.
Keywords: 330; book market; fixed price agreement; opportunity cost of reading; diversity; accessibility; competition policy